DIFFICULTIES IN TRANSLATION OF ABBREVIATIONS - Sobirova Nilufar Quvvat qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The paper discusses the differences in using abbreviations and acronyms in Uzbek  and English scientific texts, as well as difficulties of their translation and optimal strategies of interlanguage adaptation.It is demonstrated that various standards for introducing spelling, and punctuating abbreviations and acronyms in British and American scientific journals pose additional difficulties in the work of a translator in the field of science and technology, provokes translation errors and requires the use of normalization and explication as the main strategies for their translation. The paper may be of interest for those who translate scientific texts for Uzbek  and English readership.